Our unique landscape values, the sweep-pole wells in Hungary in terms of eu regulations. Heritage or curse? - Rákóczi, Attila (JOURNAL OF LANDSCAPE ECOLOGY, 2012)
This study aims at examining the present and past of one of our national values and agricultural historic relics sweep-pole wells. It also aims at examining their future in terms of the new EU regulations in agriculture and cross-compliance. This analysis investigates sweep-pole wells in the course of history and provides insight into their relationship with human society over centuries. Besides their fundamental function sweep-pole wells have obtained new roles such as communication, art, and landscape. However, owing to technical development both their importance and their number of pieces decreased by the end of the 20th century. They gradually vanished from Hungarian landscape and countryside. Then there was a significant alteration in EU regulations in agriculture and as a result of this in Hungarian regulations too, because sweep-pole wells were declared landscape elements protected by law in 2010 in accordance with cross-compliance reqirements. Accordingly, a basic data base was to be established in order to check the compliance of regulations. The point of the data base is to check the number of pieces and the state of repair of the sweep-pole wells survived till the new millenium, the time when the new regulations mentioned above were introduced. We visited all the sweep-pole wells registered in the past, and on the basis what we saw there the sweep-pole wells were categorized into four groups. The survey demonstrated that in Békés County 520 of 762 sweep-pole wells registered in the 1950’s had vanished by 2010, and 222 sweep-pole wells were either damaged or in a poor condition on their registered places. There are only 20 active sweep-pole wells operating perfectly and still in use in Békés County. In this study it was revealed that farmers are not prepared for the new regulations.
Keywords: agricultural history; national value; unique landscape value; landscape element; rural development; agricultural environment protection; cross-compliance